Relación de la Actividad Física y los Hábitos Nocivos en Estudiantes de Medicina Humana de Universidad Peruana. - Vásquez Ríos, Y.J. (2022)
Objective: determine the relationship between the level of physical activity and harmful habits of medical students at a Peruvian university in 2024. Method: 117 students were taken from a population of 210 basic science students from the medical school. To which the IPAQ (Level of physical activity), AUDIT (Risk of alcohol consumption) and Fagerström Test (Tobacco dependence) questionnaires were applied. The SPSS v.29.0.2.0 program was used in data analysis, descriptive and correlational statistics were applied using Pearson’s Chi2. Results: a significant relationship was found between physical activity and alcohol consumption (p=0,004), no significant relationship was found between the level of physical activity and tobacco dependence (p=0,639), 52,1 %. of those surveyed have a moderate level of physical activity. 68,4 % of those surveyed have a low risk of alcohol consumption and 83,7 % of those surveyed do not have the habit of smoking. Sex and year of study were statistically related to alcohol consumption, with p values of <0,001 and 0,03 respectively. There were no personal factors such as age, sex and year of study that were significantly related to tobacco consumption. Conclusions: there was only a relationship between physical activity and alcohol consumption.